Calculation of conversion coefficients using Chinese adult reference phantoms for air submersion and ground contamination. (24th February 2017) - Lu, Wei; Qiu, Rui; Wu, Zhen; Li, Chunyan; Yang, Bo; Liu, Huan; Ren, Li; Li, Junli
Abstract: The effective and organ equivalent dose coefficients have been widely used to provide assessment of doses received by adult members of the public and by workers exposed to environmental radiation from nuclear facilities under normal or accidental situations. Advancements in phantom types, weighting factors, decay data, etc, have led to the publication of newer results in this regard. This paper presents a new set of conversion coefficients for air submersion and ground contamination (with the use of Geant4) for photons from 15 keV to 10 MeV using the Chinese and International Commission on Radiological Protection (ICRP) adult reference male and female phantoms. The radiation fields, except for energy spectrum at low energies, were validated by the data obtained from the Monte Carlo code YURI. The effective dose coefficients of monoenergetic photons, obtained for the ICRP adult reference phantoms, agree well with recently published data for air submersion and ground contamination with a plane source at a depth of 0.5 g cm −2 in soil, but an average difference of 36.5% is observed for ground surface contamination with the abovementioned radiation field. The average differences in organ equivalent dose coefficients between the Chinese and the ICRP adult reference phantoms are within 6% for most organs, but noticeable differences of up to 70% or even higher are found at photon energies below 30 keV under air submersion. The effective dose coefficients obtained with the Chinese adult reference phantoms are greater than those of the ICRP adult reference phantoms above 30 keV and 0.5 MeV for ground contamination and air submersion, respectively; the average differences from the Chinese adult reference phantoms are about 3.6% and 0.4% in the whole energy range with maximum differences of 31.8% and 27.6% at 15 keV for air submersion and ground contamination respectively. These differences are attributed to anatomical discrepancies in overlying tissue mass of an individual organ and the body mass between the Chinese and the ICRP adult reference phantoms. These monoenergetic photon conversion coefficients are subsequently used to evaluate radionuclides with decay data from ICRP publication 107.